2012
DOI: 10.2478/v10247-012-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of presowing laser irradiation of seeds on sugar beet properties

Abstract: A b s t r a c t. The aim of the experiment was to establish the influence of biostimulation on the sugar beet seeds. The seeds came from the specialized breeding program energ'hill or were irradiated by the laser in two doses. The impact of the biostimulation was analyzed by determining the nitrate reductase activity and the nitrate, chlorophyll and carotenoids contents in leaves, as well as, the dry matter and sugar concentration in mature roots. The field experiment was established for two sugar beet cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…It is very important to determine the right dose. As reported by several authors (Rybinski, 2002;Gladyszewska, 2009;Hernandez-Aguilar et al, 2009;Sacala et al, 2012) the laser irradiation leads to a lower frequency of very severe or milder injuries. Serious injuries can be prevented by various, mostly low doses of irradiation (Qing-he Li et al, 2012).…”
Section: Discusion and Conclusionmentioning
confidence: 72%
“…It is very important to determine the right dose. As reported by several authors (Rybinski, 2002;Gladyszewska, 2009;Hernandez-Aguilar et al, 2009;Sacala et al, 2012) the laser irradiation leads to a lower frequency of very severe or milder injuries. Serious injuries can be prevented by various, mostly low doses of irradiation (Qing-he Li et al, 2012).…”
Section: Discusion and Conclusionmentioning
confidence: 72%
“…A positive effect of the laser light exposure on the content of sugars in sugar beet roots was observed in the studies conducted by, e.g. -Inyushin et al (1981), Koper (1994) and by Sacała et al (2012). Dobrowolski et al (1992) demonstrated an effect of laser light on the content of certain microelements in tomato fruits.…”
Section: Laser Lightmentioning
confidence: 78%
“…On the other hand, excess of energy absorbed by seeds, may accelerate plant metabolism and finally result in its growth improvement. One of the positive effects of laser biostimulation is the increased concentration of photosynthetic pigments in leaves (Sacata et al, 2012). Investigated the effects of pre-sowing seed treatments with gamma ray on the germination, emergence and seedling establishment of wheat had positive results (Hegazi and Hamideldin, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sacata et al (2012), Gadyszewska (2011), Wilczek et al (2004) used laser light as a biostimulator. During their investigations they showed effects on the growth and development of plants.…”
Section: Introductionmentioning
confidence: 99%